9y2+66y+121 = (3y+11)(3y+11) when factored
x3+27y3 = (x+3y) · (x2-3xy+9y2)
It depends on where there are parentheses, if there are any. y + 33 + 2/4 = y + 27.5 (y+3)3 + 2/4 = y3 + 9y2 + 27y + 27.5
If Y = y, then it is 9y4 or 9Y4. If Y is not the same as y, then you can't simplify it any.
-4x2 + 9y2 + 16x - 18y +29 = 0 (I hope this is what you meant) 9y2 - 18y - (4x2 -16x) +29 = 0 (group together the x's and y's, and make the x2 term positive. 9(y2 - 2y) - 4(x2 - 4x) +29 = 0 (remove common factors) 9(y - 1)2 - 1 - 4(x - 2)2 - 4 + 29 = 0 (complete the squares) 9(y - 1)2 - 4(x - 2)2 = -25 (move constants to right-hand side) [(y - 1)2] - 4[(x - 2)2]/9 = -25/9 (divide by coefficient in front of x or y bracket, in this case 9) [(y - 1)2]/4 - [(x - 2)2]/9 = -25/36 (divide by coefficient in front of other bracket, in this case 4) As you can see, we now have our equation in standard form. Our center points satisfy [(x - 2 = 0) , (y - 1 = 0)], thus our center is (2,1).
We are missing an important sign (+/-) I shall assume 9x2 - 18xy + 9y2 9(x-y)(x-y)
9y2+66y+121 = (3y+11)(3y+11) when factored
x3+27y3 = (x+3y) · (x2-3xy+9y2)
16x2 + 8x + 1 - 9y2 = (4x + 1)2 - (3y)2 which is a difference of two squares. = (4x + 1 + 3y)*(4x + 1 - 3y)
To factor a perfect square, it should be in the form a2+2ab+b2 For example: 9x2+18xy+9y2 First factor out the 9: 9(x2+2xy+y2) Make a2+2ab+b2 into (a+b)2 : 9(x+y)2
4x2-8x-9y2+54x=113(4x2-8x ) + (-9y2+54y ) =1134(x2-2x+1) -9(y2-6y+9) =113+4-81 because of distribution4(x-1)2 - 9(y-3)2 = 36Divide by 36(x-1)2 - (y-3)2 =19 4
27y3 + 125z3 = (3y + 5z)*(9y2 - 15yz + 25z2).
6xy+9y2
It depends on where there are parentheses, if there are any. y + 33 + 2/4 = y + 27.5 (y+3)3 + 2/4 = y3 + 9y2 + 27y + 27.5
(x + 3y)(x2 - 3xy + 9y2)
(4x + 3y)(4x + 3y) or (4x + 3y)2
3(2x + 3y)(2x - 3y)